Line-selective macrophage activation with an anti-CD40 antibody drives a hemophagocytic syndrome in mice - Ingoglia, Giada (Blood Adv, 2020)
Hemophagocytic syndromes comprise a cluster of hyperinflammatory disorders, including hemophagocytic lymphohistiocytosis and macrophage activation syndrome. Overwhelming macrophage activation has long been considered a final common pathway in the pathophysiology of hemophagocytic syndromes leading to the characteristic cytokine storm, laboratory abnormalities, and organ injuries that define the clinical spectrum of the disease. So far, it is unknown whether primary macrophage activation alone can induce the disease phenotype. In this study, we established a novel mouse model of a hemophagocytic syndrome by treating mice with an agonistic anti-CD40 antibody (Ab). The response in wild-type mice is characterized by a cytokine storm, associated with hyperferritinemia, high soluble CD25, erythrophagocytosis, secondary endothelial activation with multiple organ vaso-occlusion, necrotizing hepatitis, and variable cytopenias. The disease is dependent on a tumor necrosis factor-α–interferon-γ–driven amplification loop. After macrophage depletion with clodronate liposomes or in mice with a macrophage-selective deletion of the CD40 gene (CD40(flox/flox)/LysMCre), the disease was abolished. These data provide a new preclinical model of a hemophagocytic syndrome and reinforce the key pathophysiological role of macrophages.